2021
DOI: 10.3390/robotics10020072
|View full text |Cite
|
Sign up to set email alerts
|

A* Based Routing and Scheduling Modules for Multiple AGVs in an Industrial Scenario

Abstract: A multi-AGV based logistic system is typically associated with two fundamental problems, critical for its overall performance: the AGV’s route planning for collision and deadlock avoidance; and the task scheduling to determine which vehicle should transport which load. Several heuristic functions can be used according to the application. This paper proposes a time-based algorithm to dynamically control a fleet of Autonomous Guided Vehicles (AGVs) in an automatic warehouse scenario. Our approach includes a rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In [29], the D* Lite search algorithm is run on a reachability graph obtained from a suitable coloured Petri net that models feasible multi-AGV trajectories. A Time Enhanced A* search is proposed in [30] to find collision-free route plans in a time-expanded network, and integrated with tabu search techniques to further improve the efficiency by changing the assignment of transport tasks between robots. The Conflict Based Search proposed in [31], and further enhanced in [32], explores a constraint tree whose nodes are evaluated through nominal shortest routes and, in case of collisions, branches are generated corresponding to alternative vehicle priorities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [29], the D* Lite search algorithm is run on a reachability graph obtained from a suitable coloured Petri net that models feasible multi-AGV trajectories. A Time Enhanced A* search is proposed in [30] to find collision-free route plans in a time-expanded network, and integrated with tabu search techniques to further improve the efficiency by changing the assignment of transport tasks between robots. The Conflict Based Search proposed in [31], and further enhanced in [32], explores a constraint tree whose nodes are evaluated through nominal shortest routes and, in case of collisions, branches are generated corresponding to alternative vehicle priorities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Achieving the large-scale use of automatic guided vehicles (AGVs) called for by Industry 4.0 is a daunting undertaking. Most AGVs nowadays are used in massive industries, such as Amazon, Alibaba, Lotte, Carrefour, Walmart, and Pinduoduo [1][2][3][4][5][6]. AGVs have shown great benefits in the logistics field and have led to a significant reduction in handling and transportation costs.…”
Section: Introductionmentioning
confidence: 99%
“…The studies in [3,27,28] examined the roles of AI, robotics, and data mining in AGV navigation, and concluded that effective algorithms for navigating indoor spaces rely heavily on the extraction of appropriate local features for performing keyframe selection, localization, and relative posture calculation. Many features and feature processing methods have been proposed, including segments of invariant column [4], SIFT (Scale Invariant Feature Transform) [29,30], and FREAK (Fast Retina Keypoint) [29].…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle is able to sense its surroundings using sensors (ultrasonic, infrared, etc.). A robotic vehicle can be controlled manually (the operator controls the vehicle manually) or autonomously (the vehicle moves along a designated path) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%